1997
DOI: 10.1093/oxfordjournals.jhered.a023125
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization Between Tammar Wallaby (Macropus eugenii) Populations From Western and South Australia

Abstract: Populations of tammar wallabies (Macropus eugenii) occur in southwest Western Australia and on five Australian offshore islands, four in Western Australia and one in South Australia. The South Australia and Western Australia populations have probably been isolated from each other for 50,000-100,000 years. Studies have shown that there are morphological and genetic differences between these populations. Attempts at mating individuals from Garden Island (Western Australia) with individuals from Kangaroo Island (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…By discounting extant Australian populations as origins for the New Zealand founders, we have earmarked them as an important conservation resource for potentially restoring lost taxonomic diversity in Australia via reintroduction. population as the only extant representative of the South Australian tammar (McKenzie & Cooper, 1997). In the meantime instigation of a reintroduction program may be prudent, on the basis of the apparent uniqueness of the tammars in New Zealand, which have attained pest status and at various times are actively controlled (Warburton, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…By discounting extant Australian populations as origins for the New Zealand founders, we have earmarked them as an important conservation resource for potentially restoring lost taxonomic diversity in Australia via reintroduction. population as the only extant representative of the South Australian tammar (McKenzie & Cooper, 1997). In the meantime instigation of a reintroduction program may be prudent, on the basis of the apparent uniqueness of the tammars in New Zealand, which have attained pest status and at various times are actively controlled (Warburton, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite their genetic divergence at neutral loci, SA and WA tammar wallabies are known to be fully inter-fertile (in captivity), with F1 and back-cross hybrids of both sexes showing normal fertility [28]. This is quite unlike the similarly divergent eastern and western grey kangaroos, where both pre- and post-mating reproductive isolation is more developed, including male hybrid sterility [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Previous genetic comparisons of the Kangaroo Island (SA) and Garden Island (WA) populations, using several techniques, revealed substantial differentiation (reviewed in [5], see also [25,26,27]), although captive mating trials demonstrated the complete fertility of F1 and back-cross hybrids of both sexes [28]. This combination of attributes was subsequently exploited [29] to enable the construction of the first comprehensive physical linkage map for a marsupial [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The same reasoning can be applied to interactions between embryonic genes, which are extensively expressed by the paternal genome in the trophoblast and placenta (Constancia et al 2004), and maternal tissues of the mother's reproductive tract. F 2 hybrid rebound is evident in the Peromyscus crosses just discussed and appears to be a common feature of hybridization in flowering plants and mammals (Dawson 1965; Gray 1972; McKenzie & Cooper 1997; Tate et al 1997; Bradshaw et al 1998).…”
Section: Predictions and Preliminary Tests Of The Vdchmentioning
confidence: 92%